Effect of air-polishing on surface roughness of composite dental restorative material - comparison of three different air-polishing powders - Joanna Janiszewska-Olszowska; Agnieszka Drozdzik; Katarzyna Tandecka; Katarzyna Grocholewicz (BMC, 2020)
Abstract Background Increased composite roughness enhances bacterial adhesion and discoloration, thus increasing the risk of gingival inflammation and secondary caries. Concerns about detrimental effects of sodium bicarbonate on surface roughness influenced the development of less abrasive powders: a glycine-based powder and an erythritol-based powder, additionally - sodium bicarbonate-based powder of reduced grain size. However, there is limited evidence on effects of these materials on the surface of dental fillings. The aim of the present study was to compare the effects of three air-polishing powders (of a reduced abrasiveness) on surface roughness of microhybrid restorative composite material. Material and methods Microhybrid light-cure resin composite samples were placed on 64 plaster cubes and light-cured through polyester strips. Surface roughness was measured using laser confocal microscope (magnification 2160x). The specimens were randomly divided into three groups (n = 20, 20 and 24) and air-polished with: sodium bicarbonate (40 μm), glycine (25 μm) and erythritol (14 μm), respectively. Then surface roughness was remeasured, keeping the same field of observation. Specialized 3D analysis software was used for data processing. Parameters according to ISO 25178: Sa, Sq, Sku, Sp, Sv, Sz, Ssk were used to describe surface roughness. Results Sa, Sq, Sp, Sv, Sz increased significantly following air polishing. Ssk was significantly higher, whereas Sku was significantly lower in sodium bicarbonate and erythritol groups than before air polishing. Comparison between the three powders revealed that Sa was significantly higher in sodium bicarbonate group than in glycine group. Sku was significantly higher in glycine and erythritol groups than in sodium bicarbonate group. Conclusions Sodium bicarbonate has a stronger detrimental effect on composite surface than glycine or erythritol. No advantage of erythritol comparing to glycine could be found.